Bibliometric Analysis of Hospital Smoking Policies: Research Trends, Influences, and Global Collaboration - Nurlia, Nurlia; Samsimbar, Samsimbar (LPPPIPublishing, 2025)
This study aims to analyze research trend developments, scientific impact, and global collaboration patterns in the field of hospital smoking ban policies using a bibliometric approach. Data were collected from the Scopus database using relevant keywords related to